2021
DOI: 10.1038/s41467-021-21922-w
|View full text |Cite
|
Sign up to set email alerts
|

Bora phosphorylation substitutes in trans for T-loop phosphorylation in Aurora A to promote mitotic entry

Abstract: Polo-like kinase 1 (Plk1) is instrumental for mitotic entry and progression. Plk1 is activated by phosphorylation on a conserved residue Thr210 in its activation segment by the Aurora A kinase (AURKA), a reaction that critically requires the co-factor Bora phosphorylated by a CyclinA/B-Cdk1 kinase. Here we show that phospho-Bora is a direct activator of AURKA kinase activity. We localize the key determinants of phospho-Bora function to a 100 amino acid region encompassing two short Tpx2-like motifs and a phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
2
19
0
1
Order By: Relevance
“…Gao et al found that PLK1 could promotes proliferation and suppresses apoptosis of renal cell carcinoma cells by phosphorylating MCM3 27 , which suggested that PLK1 was also closely related to cell cycle and apoptosis. N. Tavernier et al found that CCNA2-CDK2 complex could activate Bora phosphorylation, and p-Bora bind to AURKA and PLK1 to form a complex that activates PLK1 expression, thus promote cell proliferation, inhibit cell apoptosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al found that PLK1 could promotes proliferation and suppresses apoptosis of renal cell carcinoma cells by phosphorylating MCM3 27 , which suggested that PLK1 was also closely related to cell cycle and apoptosis. N. Tavernier et al found that CCNA2-CDK2 complex could activate Bora phosphorylation, and p-Bora bind to AURKA and PLK1 to form a complex that activates PLK1 expression, thus promote cell proliferation, inhibit cell apoptosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a manner thematically similar to how Tpx2 binding and AURKA autophosphorylation synergize to activate AURKA at microtubules, recent work revealed that a phosphorylated form of Bora activates cytoplasmic AURKA during mitotic commitment ( Tavernier et al, 2021 ).…”
Section: Phospho-bora Activates Unphosphorylated Aurka In the Cytopla...mentioning
confidence: 99%
“…AURKA activation during mitotic commitment is critically dependent on the evolutionarily conserved protein Bora, following its own phosphorylation on a key regulatory site on Ser112. This event is essential for the phosphorylation of Plk1 on Thr210 by AURKA in vitro and for timely mitotic entry in vivo, both in Xenopus egg extracts ( Vigneron et al, 2018 ) and in human cells ( Tavernier et al, 2021 ). Remarkably, phospho-Bora binds to and potently activates AURKA lacking phosphorylation of its activation segment, suggesting the possibility that the phosphate on S112 of Bora may physically and/or functionally substitute for the phosphorylated activation segment on AURKA.…”
Section: Phospho-bora Activates Unphosphorylated Aurka In the Cytopla...mentioning
confidence: 99%
See 2 more Smart Citations